A Generalization of the bounds of copulas on quantum logic - Al-Adilee, Ahmed; Kadhem Kareem Althabhaw, Sami (International Journal of Engineering and Technology, 2018)
OurÂ Â paper is concerned with a generalization of the boundaries of copula that are well-known by Frechet-Hoeffding conditions [4], and study copula boundaries as functions defined on quantum logic ., WhileÂ there are many Â properties that have been presented according to our proposed generalization throughout these modified functions and show that some important propositions that have different forms to those of classical copulas. Indeed, it has been shown two main results relevant to the lower and upper boundaries of what we have defined and named by quantum logic copulas, see [1].Â Â